2011
DOI: 10.1096/fj.10-175992
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and epithelial cell injury in AIDS enteropathy: involvement of endoplasmic reticulum stress

Abstract: Immunosuppressive lentivirus infections, including human, simian, and feline immunodeficiency viruses (HIV, SIV, and FIV, respectively), cause the acquired immunodeficiency syndrome (AIDS), frequently associated with AIDS enteropathy. Herein, we investigated the extent to which lentivirus infections affected mucosal integrity and intestinal permeability in conjunction with immune responses and activation of endoplasmic reticulum (ER) stress pathways. Duodenal biopsies from individuals with HIV/AIDS exhibited i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
30
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 36 publications
3
30
0
1
Order By: Relevance
“…E. bieneusi was not associated with intestinal inflammation in our study, as demonstrated by the lactoferrin test in HIV negative and HIV positive individuals even though most HIV positive individuals without microsporidia had elevated lactoferrin, indicating high level of intestinal inflammation. This could be due to t h e e f f e c t o f H I V i t s e l f a s p r e v i o u s l y demonstrated (Kotler et al, 1993;Maingat et al, 2011). This is in line with some studies where multiple small intestinal biopsies showed atrophy with acute and chronic inflammation in HIV seropositive individuals even without apparent pathogens (Orenstein et al, 1992;Snijders et al, 1995;Idris et al 2010).…”
Section: Discussionsupporting
confidence: 62%
“…E. bieneusi was not associated with intestinal inflammation in our study, as demonstrated by the lactoferrin test in HIV negative and HIV positive individuals even though most HIV positive individuals without microsporidia had elevated lactoferrin, indicating high level of intestinal inflammation. This could be due to t h e e f f e c t o f H I V i t s e l f a s p r e v i o u s l y demonstrated (Kotler et al, 1993;Maingat et al, 2011). This is in line with some studies where multiple small intestinal biopsies showed atrophy with acute and chronic inflammation in HIV seropositive individuals even without apparent pathogens (Orenstein et al, 1992;Snijders et al, 1995;Idris et al 2010).…”
Section: Discussionsupporting
confidence: 62%
“…These studies found that miRNA depletion was likely due to the inflam- matory environment and not direct infection of T cells (55). Chronic inflammation and increased immune activation in the GI tract during HIV/SIV infection has previously been reported, and it is possible that this is a contributing factor in decreased miRNA expression (18,58). In the present study, we sought to correlate viral loads, CD4 ϩ T cell depletion, and immune activation with loss of specific miRNA expression.…”
Section: Discussionmentioning
confidence: 90%
“…Several different potential mechanisms of intestinal EC apoptosis in SIV/HIV infection have been proposed, including virusinduced apoptosis mediated by the interaction of SIV and GPR15/ Bob, an epithelial associated coreceptor for HIV-1/SIV (39), increased infiltration of perforin-positive mucosal cytotoxic T cells (6), upregulation of inflammatory cytokines by direct interaction of ECs with HIV-1 envelope protein (58), and viral proteinand cytokine-induced endoplasmic reticulum stress (12). In conclusion, this investigation clearly indicated that internalization of IL-10R was a key feature in SIV pathogenesis where the interaction between surface IL-10R and IL-10 might be important in regulating the proinflammatory and Th1 function in SIV-infected InRMs.…”
Section: Discussionmentioning
confidence: 99%
“…Increased permeability due to compromised barrier function could facilitate gut microbiota crossing the mucosal epithelium and entering circulation (microbial translocation) (10). Epithelial injury and impaired epithelial regeneration are considered key factors in the pathogenesis of AIDS contributing to generalized HIV-induced immune cell activation (9,11,12).…”
mentioning
confidence: 99%